Psikoedukasi Tentang Kesehatan Mental Dan Psikopatologi Pada Masyarakat - Puspita Puji Rahayu; Auliya Ulil Irsyadiyah (Universitas Pahlawan Tuanku Tambusai, 2022)
Mental illness can cause problems in everyday life, not only can damage interactions or relationships with other people, but can also reduce performance in school and work productivity. Mood disorders include a variety of emotional disturbances that make a person unable to function, from the sadness of depression to the unrealistic euphoria and irritability of mania. Mood disorders are the most commonly diagnosed mental disorders in individuals with attempted suicide. So the webinar Mental Health and Psychopathology is carried out as a community service activity, as an effort to help maintain mental health in daily life and understand mood disorders and prevent suicide. The method used through several stages, namely the formation of a committee team, preparation, implementation and evaluation of activities. The results of the evaluation indicate that there are benefits received by the community and the organization of the event as a whole went well and smoothly.